Cancer in Pregnancy in Indonesia: A Global Review and 2022–2025 Cohort Analysis of Maternal and Neonatal Outcomes - Elita Rahmi; Bachnas, Muhammad Adrianes; Sri Sulistyowati (Journal of Maternal and Child Health, 2025)
Background: Cancer during pregnancy is rare but presents serious challenges, especially in low- and middle-income countries like Indonesia. Limited national data, delayed diagnosis, and lack of standardized care make management difficult. Global awareness is growing, but regional differences in outcomes remain poorly understood. This study aims to provide a comprehensive overview of cancer during pregnancy, including its clinical characteristics and maternal-fetal outcomes both in Indonesian and global data. Subjects and Method: This systematic review was conducted following PRISMA guidelines from databases of PubMed, EMBASE, Scopus, and additional search, published between 2022 and April 2025. The included studies reported the global depiction of pregnancy-associated cancer. Newcastle-Ottawa Quality Assessment Scale (NOS) was used to assess the quality of observational included studies, while the Joanna Briggs Institute checklists for assessment of case reports. Results: A total of 14 studies were included based on the criteria, with a total population of 29,403 pregnant women associated with cancer. From this systematic review, the most found cancers during pregnancy were breast cancer, cervical cancer, and ovarian cancer, both from Indonesian data and global studies. Compared to global studies, obstetric complications were more prevalent in Indonesia, including preterm birth (64% vs 52%, respectively); very preterm birth (22% vs 15%, respectively); caesarean delivery (76% vs 65%, respectively); preeclampsia (18% vs 12%, respectively); and postpartum haemorrhage (15% vs 10%, respectively). Conclusion: The global literature shows wide variation in cancer types, gestational timing, and outcomes. Indonesian cohort data show higher rates of preterm birth, low birth weight, and maternal complications compared to global averages. Delays in diagnosis and limited access to integrated cancer-obstetric care may explain these differences. The findings support the urgent need for national guidelines, early detection programs, and multidisciplinary care models for managing cancer in pregnancy in resource-limited settings.